Selective laser melting of AlSi10Mg: Influence of post-processing on the microstructural and tensile properties development. (5th September 2016) - Tradowsky, U.; White, J.; Ward, R.M.; Read, N.; Reimers, W.; Attallah, M.M.
Abstract: The study looks into the impact of thermal post-processing using Hot Isostatic Pressing (HIPping) and/or T6-peak aging treatment, post-process machining, as well as the build orientation on the microstructural and mechanical properties development in AlSi10Mg alloy fabricated using Selective Laser Melting (SLM). The builds contained fine columnar grains, with a fine Si-enriched cellular dendritic network, resulting in tensile strengths exceeding the castings. To elucidate the as-fabricated microstructure and strength, thermal modelling was employed, predicting cooling rates of 10 5 –10 6 °C/s. Voids, mostly due to oxide films, were observed using Micro-CT in the as-fabricated condition. HIPping collapsed most voids, showing virtually no trace even after a further T6 treatment. Generally, the tensile properties of the majority of conditions were significantly better than in the cast + T6 equivalent alloy. Post-process machining was also found to improve the strength (compared to the as-fabricated surface). However, HIPping + T6 allowed the builds to achieve the required tensile properties, without surface machining. By assessing the influence of powder recycling, it was found that the void content linked to oxide layer formation increased following powder recycling, resulting in a drop in tensile properties. The interaction between the microstructure, surface condition, thermal post-processing, and fracture mode is discussed. Graphical abstract: Highlights: As-fabricated tensile properties of SLMed AlSi10Mg exceed the cast properties. Horizontal samples show better tensile properties to vertical samples. HIPping + T6 or T6 only do not significantly improve the tensile properties. Powder recycling reduces the tensile properties due to oxide-film induced voids.